Fraudulently Claiming Following a Road Traffic Accident: A Pilot Study of UK Residents' Attitudes. Issue 3 (3rd May 2016) - Cartwright, Ashley; Roach, Jason
Abstract : The United Kingdom Government recently expressed concern about the financial repercussions that feigned whiplash claims following road traffic accidents (RTAs) are having on the insurance industry and the United Kingdom economy. Indeed, this is a problem that is a likely result of a significant percentage of otherwise law-abiding citizens, who interpret this behaviour to be victimless. Nevertheless, feigning illness for some external incentive is not new, and psychiatry has long battled with the problem of 'malingering'. Previous research has indicated that a substantial prevalence of malingering exists across a variety of contexts; however, establishing the ground truth of those who malinger for financial compensation is problematic. This article presents an alternative approach that provides a brief insight into the problem of malingering following a RTA. A total of 197 United Kingdom residents completed a hypothetical questionnaire that examined their likelihood of malingering with respect to depression, posttraumatic stress disorder (PTSD), or whiplash following a RTA. The results suggest that a substantial percentage of those in the present sample indicated they would be likely to malinger using either a partial malingering or a false imputation strategy. Malingering following a RTA in the United Kingdom appears to be regarded with little severity, and the present paper discusses the wider implications of the findings.